Sensory characteristics of ice cream produced in the United States and Italy - Thompson, Kelly R. (Kansas State University, 2007)
This study was conducted to define and compare typical sensory characteristics of high quality Italian gelati to ice creams produced in the United States. Highly trained descriptive sensory panelists evaluated gelato samples in Italy, purchased direct from local gelaterias, and ice cream samples in the U.S., purchased from grocery stores and local shops. In general, gelati gave higher overall fruity and fruit ID scores, chocolate gelati gave higher chocolate and cocoa notes, and vanilla gelati gave higher vanilla and lower vanillin intensities than most U.S. ice creams. Gelati were consistently associated with higher density, lower firmness, and slower meltdown. When compared to U.S. ice creams, Italian gelati were characterized by specific sensory properties: "true to type" flavors; high intensity flavors that were considered to be typical to that flavor category or specific fruit and are combined with a dense, smooth texture that allows for the development of flavor, body and bloom, enhancing the perception of flavors. The research conducted in this study may be useful for ice cream manufacturers and sensory scientists. This study is the first to define sensory characteristics of high quality Italian gelati and the information may be used to produce ice cream with increased consumer liking. The descriptive attributes developed can be used for the development of new or improved of ice cream products.
Keywords: sensory; ice cream; gelato; Agriculture, Food Science and Technology (0359)